Analysis Of Online Begging Phenomena in Tiktok (Case Study of Changes in the Structure of Social Problems About Online Beggars) - Raisha Shahana; Maria Indriani K; Detya Wiryany (West Science Interdisciplinary Studies, 2023)
This article focuses on social media TikTok so that it can have a negative impact on society, such as the emergence of the phenomenon of "online beggars" and mud baths as a form of online begging action on TikTok. This article analyzes “online beggars” who use social media as an online fundraising platform and as a way for online beggars to ask benefactors for financial assistance on TikTok. The writing method uses case studies with a qualitative approach based on New Media Theory related to technology. The author conducted an analytical study on social media TikTok regarding the activities of online beggars in social media, especially TikTok. The conclusion of this article is that the emergence of the phenomenon of "online beggars" is caused by social inequality, poverty and inability to live. This is seen from the sophistication of TikTok's social media technology which can be used as an online fundraising platform. So "online beggars" take advantage of Tiktok's social media as a place to show their misery and to attract empathy from the audience live TikTok.